Kidney Injury Molecule-1 (Kim-1) Sebagai Biomarker Dini Nefropati Diabetik Pada Pasien Diabetes Melitus Tipe 2 - Marni Tangkelangi (JURNAL INFO KESEHATAN, 2017)
Diabetic nephropathy is a chronic complication of type 2 diabetes mellitus (DM). To prevent the onset or progression of nephropathy, a biomarker is needed that can detect kidney problems at an early stage. This study aims to determine differences in urine KIM-1 levels and correlation of levels of KIM-1 with albuminuria in patients with Non-Nephropathy DM, Insipien Nephropathy and Diabetic Nephropathy and the role of KIM-1 as an early biomarker of Diabetic Nephropathy. This research was conducted at Dr. Wahidin Sudirohusodo and his networking hospital. This study used a cross-sectional design with the number of type 2 DM patients as many as 78 people who met the inclusion criteria. The results showed that KIM-1 levels in patients with Non-Nephropathy DM (albuminuria [uALB] <20 mg/L), Ineffective Nephropathy (uALB 20-300 mg / L) and Diabetic Nephropathy (uALB> 300 mg/L) respectively is 0.862 ± 0.246 ng / mL, 2.409 ± 0.816 ng/mL and 3.503 ± 0.370 ng / mL. There were differences in mean KIM-1 levels between Non Nephropathy and Nephropathy Insipid (sig = 0.000 p <0.05), Non Nephropathy and Diabetic Nephropathy (sig = 0.000 p <0.05), Insipid Nephropathy and Diabetic Nephropathy (sig = 0.000 p <0.05) Correlation between KIM-1 level with albuminuria concentration in patients with Non Nephropathy DM (r = 0.948; sig <0.05), Nephropathy Insipien (r = 0.969; sig <0.05) and Diabetic Nephropathy (r = 0.911; sig <0.05). There are levels of KIM-1 that exceed the normal limit (> 0.837 ng / mL) in patients with non-nephropathy DM (normoalbuminuria) so that KIM-1 can be considered as an early biomarker of diabetic nephropathy.